Читальні “Просвіти” в Томашівцях - Король, Т. (Україна: культурна спадщина, національна свідомість, державність, 2010)
Викладено заснування і діяльність читальні Товариства “Просвіта” у Томашівцях у 1898–1939 рр. та с. Кам’яному. Названо перших членів, кількісний склад, форми діяльності, протистояння з москвофілами. The author gives account of the establishing and activities of the reading clubs of “Prosvita” in Tomashivtsi in 1898–1939 and in the village Kamiane. He lists first members of the reading club and gives their number, clarifies forms of work and opposition to the Moscowphiles.